A Comparative study of prisoners and non-prisoners on temperamental attributes: implication on crime commission (2010)
The study compared the temperamental attributes of prisoners with non-prisons to determine particular temperamental areas where prisoners excelled as well as the least possessed by them compared with the non-prisoners. One hundred inmates of Agodi prison as well as One hundred non prisoners in Ibadan participated in the study. The main instrument used for the study was a structured temperamental questionnaire adapted from Honk (2004), t-test statistic was used to analyze the four tested hypotheses. The results revealed that no Significant difference existed between prisoners and non-prisoners on temperamental attributes; however, the mere fact prisoners excelled on choleric, melancholic and phlegmatic temperaments based on means and SD results calls for attention, and recommendation were made towards conscious remediation of temperamental excesses